Plateware and slurping influence regular consumers’ sensory discriminative and hedonic responses to a hot soup - Youssef, J; Youssef, L; Juravle, G; Spence, C (Elsevier, 2017)
Slurping (e.g., as when consuming a hot liquid such as soup) is a common practice in many parts of Asia. The practice is also encouraged amongst many professional wine and coffee tasters in order to help enhance the release of volatile aromas. Would slurping enhance flavour perception in western participants (regular consumers) too, and/or simply make them feel self-conscious? These were the key questions addressed in the present study. Specifically, we investigated the impact of slurping vs. sipping on ratings of flavour of hot soup samples served in either a bowl or mug at one of two temperatures. 207 participants (regular consumers) rated the flavour intensity of the soup, how much they liked it, and how self-consciousness they felt after having tasted each of the four samples. The results revealed that the soup was rated as having a significantly more intense flavour when it was slurped rather than sipped, though the participants also felt a little more self-conscious. Additionally, the participants preferred the soup when served from the mug rather than when served from the bowl (this difference was more pronounced for the hotter of the two soup samples), and they felt less self-conscious. Participants liked the soup significantly more when they sipped rather than when they slurped; this difference was more pronounced when participants sampled the soup from the bowl. These results therefore highlight the impact of plateware, temperature, and consumption style on our perception and enjoyment of food.